2021
DOI: 10.3389/fmars.2021.592378
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biogeochemical Regionalization of the Southern Ocean and the CCAMLR Zone 48.1

Abstract: The Southern Ocean plays a major role in the Earth’s climate, provides fisheries products and help the maintenance of biodiversity. The degree of correspondence between physical and biogeochemical spatial variability and regionalization were investigated by calculating the main physical factors that statistically explained the biogeochemical variability within the Southern Ocean and the 48.1 zone of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). The mean value of physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 108 publications
(133 reference statements)
1
6
0
Order By: Relevance
“…Previous ecoregional studies of the SO using phytoplankton, pelagic fish and echinoid species (Koubbi et al, 2010;Ardyna et al, 2017;Fabri-Ruiz et al, 2020) generally agree with the habitat complexity found by Testa et al (2021), particularly along the Antarctic coast and shelf region. The permanently open ocean zone (POOZ), on the other hand, displays more homogeneity, which is thought to be related to the connectivity of habitat provided by the continuous eastward flow of the Antarctic Circumpolar Current (ACC) (Linse et al, 2006).…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…Previous ecoregional studies of the SO using phytoplankton, pelagic fish and echinoid species (Koubbi et al, 2010;Ardyna et al, 2017;Fabri-Ruiz et al, 2020) generally agree with the habitat complexity found by Testa et al (2021), particularly along the Antarctic coast and shelf region. The permanently open ocean zone (POOZ), on the other hand, displays more homogeneity, which is thought to be related to the connectivity of habitat provided by the continuous eastward flow of the Antarctic Circumpolar Current (ACC) (Linse et al, 2006).…”
Section: Introductionsupporting
confidence: 77%
“…The results of this study support the complexity presented by the latter. However, radiolarian distribution appears less complex than the patterns observed by Testa et al (2021) suggesting that radiolarians are not as sensitive to the fine-scale variability used to define the biogeochemical regions.…”
Section: Comparison To Bioregionalisation Of the Southern Oceanmentioning
confidence: 88%
See 3 more Smart Citations